Pengaruh Keputusan Investasi, Keputusan Pendanaan, dan Profitabilitas Terhadap Nilai Perusahaan - Yulianti, Ayundha Kusuma; Sundari, Siti (Gorontalo Accounting Journal, 2023)
This research aims to examine and demonstrate the influence of investment decisions, financing, and profitability on the company's value in the food and beverages sector on the Indonesia Stock Exchange. The company's value in this study is measured using Tobin's Q formula. The research sample consists of 18 companies selected through purposive sampling. Data analysis techniques employed in this study include descriptive statistics, multiple linear regression, coefficient of determination test, t-test, and goodness-of-fit test using the SPSS program. The research findings indicate that investment decisions contribute to an increase in company value. Financing decisions contribute to the enhancement of company value. Profitability contributes to the increase in company value.